Population Control and Family Planning Have an Important Role in Determining Birth Rate Control - Windu Budiati (Universitas STRADA Indonesia, 2023)
The affairs of population control and family planning have an important role in achieving optimal community welfare. If the family planning program in an area is successful, the demographic bonus age will be longer and will have an impact on welfare development. The purpose of this research is to find out that population control and family planning efforts have an important role in determining birth rate control. This type of research is descriptive with a qualitative approach method, taking secondary data from reports from the Population Control and Family Planning Sector results from January - December 2022 Respondents Head of Population Control and Family Planning Division, Functional Officer of Population Control, Functional Officer of Family Planning and Reproductive Health and Functional Officer of Empowerment and Family Planning Office of Health, Population Control and Family Planning of Tuban Regency.